ETHICAL BOUNDARIES OF GENETIC ENGINEERING PATENTS IN INDONESIA AND MALAYSIA - Hari Sutra Disemadi; Nor Akhmal Hasmin; David Tan; Windi Afdal; Nadia Carolina Weley (Faculty of Law, Universitas Diponegoro, 2026)
Genetic engineering increasingly pushes the boundaries of science, technology, and ethics by raising difficult questions about the acceptable limits of human intervention in living organisms. Its relationship with intellectual property law is particularly complex because patent protection is intended to reward innovation and encourage scientific development, while also being constrained by ethical limits expressed through ordre public and morality principles. This study examines how Indonesian and Malaysian intellectual property law regulate patent protection for genetic engineering inventions, particularly in relation to ethical safeguards. Using doctrinal legal research with a comparative approach, this study analyses the relevant patent statutes, legal concepts, and regulatory structures in both jurisdictions. The findings show that Indonesia provides a relatively stronger legal basis than Malaysia, mainly because its patent framework contains more developed definitions concerning invention, technology, and scientific methods. These definitions create broader conceptual space for recognising genetic engineering as a patentable field while also allowing ethical considerations to be developed through implementing regulations. However, Indonesia still lacks concrete examination standards and operational mechanisms for assessing ethical risks in genetic engineering patents. Malaysia, by contrast, recognises ordre public and morality clauses only at a general level and primarily uses them as grounds for refusing patent applications. Its legal framework also provides only limited acknowledgement of the patentability of genetic engineering inventions, especially in relation to microorganisms, without establishing a clear ethical review mechanism. This study argues that both jurisdictions require stronger normative and institutional safeguards to ensure that patent protection for genetic engineering does not undermine public morality, human dignity, environmental integrity, or broader public interest. Indonesia should develop implementing regulations and patent-examination guidelines that translate its broader amended patent definitions into concrete ethical safeguards. Malaysia should amend the Patents Act 1983 to provide an explicit ethical review mechanism for genetic-engineering-derived microorganism patents and clearer standards for applying ordre public and morality exclusions.